(untitled) (GIST – Education and Learning Research Journal, 2015)
This article reports the preliminary findings of an action research on the effects of autonomy on a group of university students at the post-graduate level taking their first Spanish course through the Content and Language Learning (CLIL) methodology. The participants, whose Spanish was at the low/mid intermediate level (ACTFL, 2012), were exposed to content related to their Masters’ degrees at a university in the United States. The sample consisted of 13 students in the experimental group and 14 in the control group. Results showed that students in the experimental group who followed a CLIL class experienced more autonomy than students in the control group who followed a more traditional class with a textbook. Pedagogical implications reflect advantages of planning curriculum according to the students’ interests and career objectives.